2018
DOI: 10.1101/508440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Dyspnea in Lung Cancer Survivors Following Curative-Intent Therapy

Abstract: word count 250)Purpose Dyspnea is highly-prevalent in lung cancer survivors following curative-intent therapy. We aimed to identify clinical determinants of dyspnea and characterize its relationship with functional exercise capacity (EC). MethodsIn an analysis of data from a cross-sectional study of lung cancer survivors who completed curative-intent therapy for stage I-IIIA disease ≥1 month previously, we tested a thorough list of comorbidities, lung function, and lung cancer characteristics. We assessed dysp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…12 A prospective study was recently completed which showed that dyspnea symptoms worsen at 1 to 3 mo following curative-intent lung cancer treatment. 53 As such, it is postulated that in order to maximize efforts to improve exercise, function, and QoL in lung cancer survivors following curative-intent treatment, optimizing medical therapy for cardiopulmonary disease 54 and possibly psychiatric illness 55 to alleviate dyspnea may also be important. Recent randomized controlled trials in patients with COPD have shown that combination long-acting muscarinic-antagonist and β -agonist inhaler therapy is effective in reducing dyspnea 56 and, possibly, in improving physical activity.…”
mentioning
confidence: 99%
“…12 A prospective study was recently completed which showed that dyspnea symptoms worsen at 1 to 3 mo following curative-intent lung cancer treatment. 53 As such, it is postulated that in order to maximize efforts to improve exercise, function, and QoL in lung cancer survivors following curative-intent treatment, optimizing medical therapy for cardiopulmonary disease 54 and possibly psychiatric illness 55 to alleviate dyspnea may also be important. Recent randomized controlled trials in patients with COPD have shown that combination long-acting muscarinic-antagonist and β -agonist inhaler therapy is effective in reducing dyspnea 56 and, possibly, in improving physical activity.…”
mentioning
confidence: 99%